2013
DOI: 10.1016/j.biocel.2013.05.035
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms and signaling pathways of angiotensin II-induced muscle wasting: Potential therapeutic targets for cardiac cachexia

Abstract: Cachexia is a serious complication of many chronic diseases, such as congestive heart failure (CHF) and chronic kidney disease (CKD). Many factors are involved in the development of cachexia, and there is increasing evidence that angiotensin II (Ang II), the main effector molecule of the renin-angiotensin system (RAS), plays an important role in this process. Patients with advanced CHF or CKD often have increased Ang II levels and cachexia, and angiotensin-converting enzyme (ACE) inhibitor treatment improves w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
129
1
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(134 citation statements)
references
References 131 publications
(165 reference statements)
2
129
1
2
Order By: Relevance
“…The loss of cardiac mass in chronic diseases such as cancer, heart failure, and obstructive pulmonary disease has been extensively reported [29][30][31][32][33][34], but the mechanisms responsible for this process are only partially elucidated [35]. In rats implanted with Walker-256 tumours -a carcinosarcoma of the mammary glands of pregnant rats [36] -tumour growth occurred quickly, causing progressive weight loss and leading to cachexia syndrome within only5 days.…”
Section: Discussionmentioning
confidence: 99%
“…The loss of cardiac mass in chronic diseases such as cancer, heart failure, and obstructive pulmonary disease has been extensively reported [29][30][31][32][33][34], but the mechanisms responsible for this process are only partially elucidated [35]. In rats implanted with Walker-256 tumours -a carcinosarcoma of the mammary glands of pregnant rats [36] -tumour growth occurred quickly, causing progressive weight loss and leading to cachexia syndrome within only5 days.…”
Section: Discussionmentioning
confidence: 99%
“…27 One of the most important pathways responsible for intracellular degradation of striated muscle proteins is the ubiquitin-proteasome system. [28][29][30] During ubiquitination, damaged cytosolic proteins are linked to ubiquitin molecules and targeted toward the proteasome, where they are cleaved into short peptides and aminoacids. 31 In heart failure, immunological and neurohormonal activation, as well as increased reactive oxygen species levels, stimulate nuclear factor-κB, which activates the ubiquitin proteasome system.…”
Section: Imbalance Between Anabolic and Catabolic Processesmentioning
confidence: 99%
“…27,48 Experimental studies have shown that AII can contribute to muscle wasting by increasing protein breakdown, reducing protein synthesis, and inhibiting muscle regenerative processes. 28,49 More recently, the role of neurohormonal activation has also been evaluated in noncardiac cachexia. In liver cancer rats, β-blocker or aldosterone antagonism has increased survival and improved cancer-induced cardiac dysfunction.…”
Section: Neurohormonal Alterationsmentioning
confidence: 99%
“…Mechanistically, reactive oxygen species and IGF-1 lead to apoptosis and protein degradation and therefore muscle wasting [50,51], which reveals the Angiotensin IIInfusion as an uncommon model for muscle wasting.…”
Section: Hormonesmentioning
confidence: 99%
“…In these KPC-mice, pancreatic adenocarcinoma develops with median survival of five months [13]. Underlying molecular mechanisms involve increased levels of Atrogin-1 and MuRF1 [49][50][51][52].…”
Section: Cancermentioning
confidence: 99%